Attempt to determine the prevalence of two inborn errors of primary bile acid synthesis: results of a European survey - Jahnel, Jörg; Haas, Dorothea (2017)
Objective: Inborn errors of primary bile acid (BA) synthesis are genetic cholestatic disorders leading to accumulation of atypical BA with deficiency of normal BA. Unless treated with primary BA, chronic liver disease usually progresses to cirrhosis and liver failure before adulthood. We sought to determine the prevalence of 2 common disorders, 3β-hydroxy-Δ5-C27-steroid dehydrogenase (3β-HSD) and Δ4-3-oxosteroid-5β-reductase (Δ4-3-oxoR) deficiencies and to describe current diagnostic and treatment strategies among different European paediatric hepatology centres. Methods: A total of 52 clinical paediatric centres were approached and 39 centres in 21 countries agreed to participate in the Web-based survey. The survey comprised questions regarding general information, number of cases, diagnostic, and therapeutic management. Results: Seventeen centres located in 11 countries reported patients with inborn errors in primary BA synthesis, 22 centres never had cases diagnosed. In total, we could identify 63 patients; 55 with 3β-HSD and 8 with Δ4-3-oxoR deficiency in 21 countries. The minimum estimated combined prevalence of these diseases was 1.13 cases per 10 million (0.99 and 0.14 for 3β-HSD and Δ4-3-oxoR deficiencies, respectively). The surveyed colleagues indicated their main challenges to be the rarity of diseases and the lack of convenient laboratory facilities nearby. Conclusion: We have identified the largest cohort of patients with 3β-HSD or Δ4-3-oxoR deficiency described so far. These diseases are likely underdiagnosed mainly due to unawareness of their existence and the lack of laboratory facilities.
Originally published: June 1, 2017
Gesehen am 02.07.2018